Structural-Functional Glaucoma Progression Trajectory in 2-Dimensional Space. Issue 4 (18th April 2022) - de Gainza, Agustina; Morales, Esteban; Salazar, Diana; Yu, Fei; Afifi, Abdelmonem; Nouri-Mahdavi, Kouros; Caprioli, Joseph
Abstract : Précis: We describe a method that provides rapid visualization of glaucomatous change in a 2-dimensional (2D) structural and functional (S/F) space. Purpose: To describe a method to visualize glaucomatous change in a 2D S/F space. Design: This was a retrospective longitudinal observational study. Subjects: Group I included 64 normal and 64 glaucomatous eyes used to develop the structural score. Group II included 957 glaucomatous eyes used to plot the structural-functional progression vectors. Methods: Subjects were arranged in 2 groups. Group I was a cross-sectional group used to develop a structural score which were applied to longitudinal measurements of patients in group II for vectoral analysis. Visual field index was used as a functional score. Vectors were created for each eye to define structural (x) and functional (y) progression. The structural and functional components were calculated with linear models of optical coherence tomography scores and visual field index. The resultant vector and its confidence interval were plotted in 2D S/F space. Main Outcome Measures: Combined structural-functional glaucomatous progression. Results: Group I included 64 normal and 64 glaucomatous eyes. We calculated 957 vectors (957 eyes of 582 OAG patients) in group II. The mean (±SD) follow-up period was 6.9 (±1.5) years and mean baseline mean deviation (MD) was −4.3 (±5.4). Preperimetric, mild, moderate, and severe groups included 159, 288, 299, and 211 eyes, respectively. Mean baseline MDs in these groups were 0.8, −1.0, −3.7, and −11.2 dB, and mean vector slopes were 0.88, 1.00, 1.98, and 2.69. Conclusion: We present a method that presents glaucoma progression in a 2D S/F space. This approach integrates a large amount of longitudinal numerical data and provides the clinician with a rapid and intuitive summary of the patient's glaucoma trajectory.